金属带式无级变速器的研究综述 - 王幼民; 唐铃凤 (Jixie chuandong)
Metal pushing V-Belt continuously Variable transmission （CVT） is the ideal transmission for automobile, it is also one of the most important research items of researches and automobile companies all over the world. The development history of metal pushing V-Belt CVT is introduced. The researches importance of metal pushing V-Belt CVT is discussed. The current status of the researche is studied. The control strategy developing tendency of CVT electro-hydraulic servo system is analyzed.